Inhibition of hepatitis C virus replication by chalepin and pseudane IX isolated from Ruta angustifolia leaves - Achmad, Fuad (Elsevier, 2014)
Hepatitis C virus (HCV) infection is highly prevalent among global populations, with an estimated number of infected patients being 170 million. Approximately 70–80% of patients acutely infected with HCV will progress to chronic liver disease, such as liver cirrhosis and hepatocellular carcinoma, which is a substantial cause of morbidity and mortality worldwide. New therapies for HCV infection have been developed, however, the therapeutic efficacies still need to be improved. Medicinal plants are promising sources for antivirals against HCV. A variety of plants have been tested and proven to be beneficial as antiviral drug candidates against HCV. In this study, we examined extracts, their subfractions and isolated compounds of Ruta angustifolia leaves for antiviral activities against HCV in cell culture. We isolated six compounds, chalepin, scopoletin, γ-fagarine, arborinine, kokusaginine and pseudane IX. Among them, chalepin and pseudane IX showed strong anti-HCV activities with 50% inhibitory concentration (IC50) of 1.7 ± 0.5 and 1.4 ± 0.2 μg/ml, respectively, without apparent cytotoxicity. Their anti-HCV activities were stronger than that of ribavirin (2.8 ± 0.4 μg/ml), which has been widely used for the treatment of HCV infection. Mode-of-action analyses revealed that chalepin and pseudane IX inhibited HCV at the post-entry step and decreased the levels of HCV RNA replication and viral protein synthesis. We also observed that arborinine, kokusaginine and γ-fagarine possessed moderate levels of anti-HCV activities with IC50 values being 6.4 ± 0.7, 6.4 ± 1.6 and 20.4 ± 0.4 μg/ml, respectively, whereas scopoletin did not exert significant anti-HCV activities at 30 μg/ml.